South Asian writers in twentieth-century Britain : culture in translation Author: - Ranasinha, Ruvani (Oxford University Press, 2007)
This book considers the work of South Asian writers who emigrated to, or were born in, Britain. Comparing the work of different generations, it shows how the experience of migrancy, the attitudes towards migrant writers in the literary market place, and the critical reception of them, changed significantly during the twentieth century. - ;South Asian Writers in Twentieth-Century Britain is the first book to provide a historical account of the publication and reception of South Asian anglophone writing from the 1930s to the present, based on original archival research drawn from a range of publ